Desirable characteristics for teachers of High Ability/Gifted students - Alexandra da Costa Souza Martins; Eunice Soriano de Alencar (Universidade Federal de Santa Maria (UFSM), 2011)
This study investigated the desirable educational background for a teacher to work with high ability/gifted students, desirable characteristics these teachers should present and conceptions on high ability/giftedness. The participants were 20 public school teachers from a city surrounding Brasilia. Of this group, ten were elementary school teachers working with initial grades and ten were undergraduate Pedagogy teachers. A qualitative approach was used and data were collected by means of a semi-structured interview. A content analysis was then conducted. In relation to the desirable educational background for a teach of high ability/gifted students, participants indicated the need of continuous training, under graduation curriculum adapted to the theme and graduation courses in the area. The desirable features for teachers of high ability/gifted students were related to personological attributes (personality traits and intellectual ability), as well as professional characteristics. The conceptions on high ability/giftedness presented by the participants were, in general, close to those found in the literature and used as reference for this study. However, there was lack of information on how to apply the theory into real practice, as well as several wrong ideas on the topic.